Identifikasi Peserta Didik Berkebutuhan Khusus (PDBK) Slow Leaner di Sekolah Dasar - Lora Septiana; Jesi Alexander Alim; Hendri Marhadi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This study aims to determine the number of slow leaner leaners in inclusive primary schools. The method used in descriptive with a quantitative approach through observation, interviews, instruments, and document analysis techniques. The research subjects included all students from grade I to grade VI. The observation result showed that out of a total of 310 students, 28 students (8.97%) were identified as PDBK. Based on the result of interviews using the instrument, 16 PDBK (57.14%) were identification showed that most of the PDBK were in the borderline and mental detective categories based on the results of psychologist referrals. This research is expected to serve as a basis for schools in designing more inclusive learning programmes and providing appropriate interventions to meet the needs of slow leaner PDBK.